2019
DOI: 10.1016/j.nicl.2019.101824
|View full text |Cite
|
Sign up to set email alerts
|

Hippocampal CA1 subfield predicts episodic memory impairment in Parkinson's disease

Abstract: Objective Parkinson's disease (PD) episodic memory impairments are common; however, it is not known whether these impairments are due to hippocampal pathology. Hippocampal Lewy-bodies emerge by Braak stage 4, but are not uniformly distributed. For instance, hippocampal CA1 Lewy-body pathology has been specifically associated with pre-mortem episodic memory performance in demented patients. By contrast, the dentate gyrus (DG) is relatively free of Lewy-body pathology. In this study, we used ultra-h… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

2
41
1
1

Year Published

2019
2019
2024
2024

Publication Types

Select...
6
1

Relationship

0
7

Authors

Journals

citations
Cited by 51 publications
(45 citation statements)
references
References 54 publications
2
41
1
1
Order By: Relevance
“…In patients with AD, the CA1 region was severely affected by neuron number and neurofibrillary tangle, which were significantly related to CDR scores [43]. A recent autopsy study also found that the degree of Lewy body pathology in CA1, but not CA2, predicted pre-mortem episodic memory impairment in patients with Lewy body dementia and Parkinson's disease [5,44]. Their findings suggested that CA1 might be more functionally relevant than CA2 and subiculum regions in memory impairment.…”
Section: Discussionmentioning
confidence: 96%
See 2 more Smart Citations
“…In patients with AD, the CA1 region was severely affected by neuron number and neurofibrillary tangle, which were significantly related to CDR scores [43]. A recent autopsy study also found that the degree of Lewy body pathology in CA1, but not CA2, predicted pre-mortem episodic memory impairment in patients with Lewy body dementia and Parkinson's disease [5,44]. Their findings suggested that CA1 might be more functionally relevant than CA2 and subiculum regions in memory impairment.…”
Section: Discussionmentioning
confidence: 96%
“…The hippocampus, as a structure playing a key role in cognitive processes, is known to remain central to the understanding of the Alzheimer's disease (AD) pathophysiology with sensitivity to the neurofibrillary tangle development and a strong association with progression to AD [1][2][3]. It is widely recognized that the hippocampus is heterogeneous and can be divided into subregions with different functions and vulnerabilities to neurodegenerative diseases [4][5][6]. While the hippocampal subregions are thought to exhibit distinct functions, the neural substrate for aberrant functionalities remains elusive.…”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation
“…CA1 receives inputs from the DG and CA3 along the perforant path. CA1 has been specifically linked to episodic memory 14 , as well as memory retrieval and consolidation [15][16][17][18][19] , suggesting that those processes may be uniquely impacted by cannabis use. Additionally, the subfields that make up the subicular complex (subiculum, parasubiculum, presubiculum) were also associated with cannabis use.…”
Section: Discussionmentioning
confidence: 99%
“…Throughout these three divisions, the hippocampus consists of several histologically differing subfields that are interconnected through a number of pathways that pass information in and out of the hippocampus through the entorhinal cortex, and among the subfields of the hippocampus 11,12 . The hippocampal subfields have been shown to fulfill different roles in the memory processes conducted in the hippocampus; for example, the dentate gyrus and third section of the cornu ammonis (CA3) having been found to be involved in memory encoding 13 and early retrieval, while the first section of the cornu ammonis (CA1) has been linked with episodic memory 14 , memory consolidation, late retrieval, and recognition [15][16][17][18][19] . In the first study to examine the association of cannabis with hippocampal subfields, Chye et al 20 used Freesurfer's automated segmentation software (https://surfer.nmr.mgh.harvard.edu) to find many subfields of the hippocampus differentiated 39 cannabis dependent individuals from 35 non-users: CA1, CA2, CA3, CA4 and the dentate gyrus (DG).…”
Section: Introductionmentioning
confidence: 99%